Evaluation of immune infiltration in the colonic mucosa of patients with ipilimumab-related colitis. (1st September 2016) - Arriola, Edurne; Wheater, Matthew; Lopez, Maria Antonette; Thomas, Gareth; Ottensmeier, Christian
ABSTRACT: Approximately 30% of patients treated with ipilimumab will develop gastrointestinal toxicity. The immunological drivers that underpin the clinical observations in human tissues are poorly understood. We report here on the immune consequences of ipilimumab treatment in the colorectal mucosa of patients with treatment-related colitis. Using immunohistochemistry, we evaluated the immune infiltrate by CD8 +, FoxP3, and granzyme B (GzmB) in colonic biopsies from 20 patients with ipilimumab-related colitis. We assessed 10 cases with normal colon biopsies for comparison. In eight cases (four on steroids only, four on steroids and infliximab), we evaluated two sequential biopsies. We observed that CD8 +, FoxP3 +, and GzmB T cell counts were significantly higher in patients with ipilimumab-related colitis compared to normal colon ( p < 0.0001). Patients who required infliximab for the resolution of their colitis had a significantly higher CD8 + /FoxP3 ratio than those treated only with steroids and this correlated with clinical severity. The analysis of repeat samples revealed that resolution of the colitis was associated with a decrease in CD8 + and FoxP3 + cells both in patients treated with steroids and infliximab. Our data suggest that counts of cytotoxic T cells and Tregs in the colonic mucosa from patients with ipilimumab-related colitis correlate with clinical findings and may predict severity and guide management.